Influence of water phase condition on microorganisms growth in butter with pectin additive - Rashevska, Tamara (My University, 1998)
As a result of scientific work, there was studied the influence of pectine additive on water phase condition and on microorganisms growth in butter. There was fixes high moisture adsorption of pectine in butter plasma, thus increasing the dispersion of moisture in butter.
Keywords: butter; pectin; water phase; сливочное масло; пектин; водная фаза; вершкове масло; водна фаза; кафедра технології молока і молочних продуктів